Carbapenem-producing Enterobacteriaceae in mothers and newborns in southeast Gabon, 2022 - Dos Santos, Sandra; Moussounda, Mesmin; Togola, Moussa; Avoune Nguema, Evelyne; Matteya, Christiane; Bignoumba, Michelle; Onanga, Richard; Lekana-Douki, Jean-Bernard; François, Patrice; van der Mee-Marquet, Nathalie (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Infections caused by carbapenemase-producing Enterobacteriaceae (CPE) pose a significant threat, leading to severe morbidity and mortality among newborns. Methods This study, conducted at Franceville hospital's maternity and neonatology wards from February 22nd to June 20th, 2022, investigated the prevalence of CPE in 197 parturients and 203 newborns. Rectal swabs were taken from parturients before delivery and from newborns 30 minutes after birth. Blood culture samples were collected if signs of infection were observed in newborns during a 28-day follow-up. A total of 152 environmental samples were obtained, comprising 18 from sinks, 14 from incubators, 27 from cradles, 39 from maternal beds, 14 from tables and desks, four from the two baby scales and 36 from bedside furniture. Results None of the 203 newborns were found to be CPE carriers 30 minutes after delivery. CPE carriage was found in 4.6% of mothers. When comparing colonized and uncolonized parturients, well-established risk factors for CPE carriage, such as recent hospitalization and antibiotic therapy, were more frequently observed among CPE carriers (33.3 vs 10.6% for hospitalization in the past 15 days; 55.5 vs 30.3% for hospitalization during pregnancy, and 55.5 vs 35.1% for antibiotic therapy during pregnancy). Notably, the prevalence of treatment with amoxicillin and clavulanic acid was 44.4% in CPE carriers compared to 17.0% in non-carriers. The incidence density of CPE-associated bloodstream infection was 0.49 per 100 newborns, accounting for a fatal case of CPE-associated bacteremia identified in one of the 203 newborns. Seven environmental samples returned positive for CPE (5 sinks and two pieces of furniture). Whole genome sequencing, performed on the 25 CPE isolates, revealed isolates carrying blaNDM-7 (n=10), blaNDM-5 (n=3), blaOXA181 (n=10), blaOXA48 (n=2) or blaOXA244 (n=1), along with genetic traits associated with the ability to cause severe and difficult-to-treat infections in newborns. Core genome comparison revealed nine CPE belonging to three international high-risk clones: E. coli ST410 (four mothers and a sink), two E. coli ST167 (a mother and a piece of furniture), and K. pneumoniae ST307 (a sink and a piece of furniture), with highly similar genetic backgrounds shared by maternal and environmental isolates, suggesting maternal contamination originating from the environment. Discussion Our study reveals key findings may guide the implementation of infection control measures to prevent nosocomial infections in newborns: the prevalence of CPE carriage in one out of 20 parturients, an infection occurring in one out of 400 newborns, substantial contamination of the care environment, clinical and environmental CPE isolates possessing genetic traits associated with the ability to cause severe and challenging infections, and clonal relationships between clinical and environmental isolates suggesting CPE spread within the wards, likely contributing to the acquisition and colonization of CPE by parturients during pregnancy.